Rural America - Kley, Antje 1968-; Paul, Heike (American studies, 2015)
"The United States was born in the country", Richard Hofstadter once wrote, "and remained emotionally attached to it long after it had moved away", David B. Danbom added in his 'History of Rural America'. Thus it may be argued that the study of American culture and civilization, first and foremost, needs to make sense of the rural. This multidisciplinary volume focuses on rural America, on areas seemingly apart from the political, economic, and cultural centers of the nation. Despite this apparent marginality, the rural often proves to be constitutive not only of regional but also of other sub
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2013 -- Erlangen; Ländlicher Raum; Landleben; Literatur; USA; Geschichte; Kultur